Burnout syndrome and resilience in medical students from a Brazilian public college in Salvador, Brazil - Dias,Alan Roger (2022)
Abstract Introduction Burnout syndrome is highly prevalent among medical students. Whereas burnout syndrome has been associated with negative outcomes, like suicidal ideation, protective factors are still unknown. Objective To evaluate if there is an association between burnout syndrome and resilience in medical students, assessing covariates such as depressive symptoms, suicidal ideation, and religiosity. Method This cross-sectional study was carried out with a sample of 209 students from a medical school in Brazil. Burnout syndrome was assessed using the Maslach Burnout Inventory – Student Survey. Potential protective factors and aggravators to burnout syndrome were investigated using appropriate scales. Results Fifty-nine students (28.2%) presented burnout. Multivariate analysis showed that resilience was a protective factor (p < 0.001), along with being older, married or having better academic performance. Depressive symptoms were positively associated with burnout. Religiosity was not a protective factor and suicidal ideation was not associated with burnout when adjusted for depressive symptoms. Conclusion Burnout is frequent among medical students, impacting mental health and academic performance. Resilience seems to be a protective factor, and the relationship between burnout and suicidal ideation is possibly mediated by depressive symptoms. Prospective studies are needed to further investigate the associations found in this study.